Effect of Squeeze Casting on Microstructure and Mechanical Properties of Hypereutectic Al-xSi Alloys. Issue 4 (April 2017) - Li, Runxia; Liu, Lanji; Zhang, Lijun; Sun, Jihong; Shi, Yuanji; Yu, Baoyi
Abstract : The effect of squeeze casting on microstructure and mechanical properties of hypereutectic Al- x Si alloys ( x  = 15, 17.5, 22 wt%) was investigated in this study. Results show that microstructure of the hypereutectic Al-xSi alloys was obviously improved by squeeze casting. The amount of coarse primary Si phase decreased, while that of fine primary α-Al dendrites increased with the increase of squeeze casting pressure. Due to the decrease of coarse primary Si particles, cracking of the matrix was reduced, whilst the fine microstructure, and mechanical properties of the squeeze casting alloys were improved. Compared with gravity casting alloys, mechanical properties of the hypereutectic Al-xSi alloys solidified at 600 MPa were improved significantly. Hardness of the squeeze casting hypereutectic Al-(15, 17.5, 22 wt%) Si alloys was improved by 15.91%, 12.23%, 17.48%, ultimate tensile strength was improved by 37.85%, 32.27%, 22.74%, and elongation was improved by 55.83%, 167.86%, 126.76%, respectively. Due to the uniform distribution of Si phases in squeeze casting Al-xSi alloys, their wear resistance was markedly enhanced.